Lack of Stability of Aggregates after Thrombin-Induced Reaggregation of Thrombin-Degranulated Platelets - Kinlough-Rathbone, Raelene L; Packham, Marian A; Perry, Dennis W; Mustard, J Fraser; Cattaneo, Marco (Thrombosis and Haemostasis, 1992)
The stability of platelet aggregates is influenced by the extent of the release of granule contents; if release is extensive and aggregation is prolonged, deaggregation is difficult to achieve. The relative importance of the contributions of released substances to aggregate stability are not known, although stable thrombin-induced aggregates form in platelet-rich plasma from patients with barely detectable plasma or platelet fibrinogen, and ADP stabilizes thrombin-induced aggregates of platelets from patients with delta storage pool deficiency which otherwise deaggregate more readily than normal platelets. We degranulated platelets with thrombin (0.9 U/ml caused greater than 90% loss of delta and alpha granule contents) and recovered them as individual platelets in fresh medium. The degranulated platelets were reaggregated by thrombin (2 U/ml). To prevent continuing effects of thrombin, FPRCH2C1 was added when thrombin-induced aggregation of thrombin-degranulated platelets reached its maximum. EDTA (5 mM) or EGTA (5 mM) added at maximum aggregation did not deaggregate these platelets, indicating that the stability of these aggregates does not depend on Ca2+ in the medium. Whereas with control platelets a combination of PGE1 (10 μM) and chymotrypsin(10 U/ml) was required for deaggregation, with thrombin-degranulated platelets either PGE1 or chymo-trypsin alone caused extensive deaggregation. The rate and extent of deaggregation of thrombin-degranulated platelets by a combination of PGE1 and chymotrypsin was greater than with control platelets.Electron microscope gold immunocytochemistry using antihuman fibrinogen IgG, anti-von Willebrand factor and anti-fibronectin showed a) that fibrinogen in the vacuoles of degranulated platelets was visible at focal points of platelet contact in the aggregates, but that large areas of platelet contact had no fibrinogen detectable between them; and b) in comparison to fibrinogen, little fibronectin or von Willebrand factor (vWf) was detectable in the platelets.Since the linkages between thrombin-degranulated platelets reaggregated by thrombin can be disrupted either by raising cAMP (thus making glycoprotein IIb/IIIa unavailable) or by proteolysis, these linkages are less stable than those formed between normal platelets. It might therefore be expected that platelets that take part in thrombus formation and then recirculate are likely to form less stable thrombi than platelets that have not released their granule contents.